THE ROLE OF UNEP (UNITED NATIONS ENVIRONMENT PROGRAMME) IN PEATLAND CONSERVATION IN SOUTH TAPANULI - Ramadhani, Atika; Fuadi, Ahmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This study delves into the pivotal role undertaken by UNEP in tackling environmental crises, with a specific focus on the preservation of peatlands. Peatlands stand as critical ecosystems, playing a dual role in climate crisis mitigation and, conversely, significantly exacerbating global warming if subjected to degradation. UNEP's endeavors in peatland conservation extend to nations harboring extensive peatlands, as exemplified by Indonesia, particularly spotlighting the Tapanuli Selatan region through the implementation of the Ecosystem-based Disaster Risk Reduction (Eco-DRR) project. Within this locale, peatlands are prone to recurrent and protracted flooding, peat fires, and land subsidence attributed to peat desiccation and heightened susceptibility to conflagrations. In dissecting this case study, the research applies Harold K. Jacobson's theoretical framework concerning the functions of international organizations, affording a deeper grasp of UNEP's role within this realm. Employing an explanatory qualitative methodology, the data compilation process yields comprehensive insights and comprehension. A substantial portion of the dataset stems from UNEP's publications elucidating the Eco-DRR project in Indonesia, coupled with annual reports pertaining to peatlands, scholarly volumes, and pertinent articles. The study's findings elucidate UNEP's pronounced impact through the Eco-DRR initiative, effectively realizing the five fundamental roles as delineated by Harold K. Jacobson regarding international organizations. UNEP adeptly establishes a harmonious distribution of benefits by actively engaging local communities in peatland conservation endeavors. Collaborative ventures between UNEP, local communities, regional authorities, and pertinent institutions foster innovative strategies such as Bio-Rights, instrumental in achieving multifaceted goals encompassing fire prevention, ecosystem rejuvenation, and the fortification of community resilience. Key Words: UNEP, Peatland, Eco-DRR, International Organization